Designing Critical Multilingual Multiliteracies Projects in Two-Way Immersion Classrooms: Affordances and Impacts on Students - Hyun, Jungwon; Bettney Heidt, Esther; Prasad, Gail (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2022)
Language separation policies in two-way bilingual education (TWBE) reflect ideologies of double monolingualism (Heller, 1995) and ignore the sociolinguistic realities of bi/multilingual students (García & Lin, 2017). This case study investigates the design and implementation of collaborative multilingual identity text projects (Prasad, 2018) in a Spanish-English two-way immersion (TWI) school. Identity text pedagogies (Cummins & Early, 2011) that engage bilingual students in creating dual-language multimodal texts have been taken up across a wide variety of contexts. Few studies in the United States, however, have examined how TWI teachers can use multiliteracies pedagogy (New London Group, 1996) with a critical multilingual language awareness (CMLA) focus to move beyond the frame of Spanish-English through the creation of collaborative multilingual and multimodal class books. A thematic analysis of classroom data from our case study demonstrates that implementing critical multilingual multiliteracies projects fostered students’ CMLA while building positive bi/multilingual identities, leveraged students’ linguistic repertoires beyond the language of instruction, and encouraged linguistic risk-taking. This empirical study highlights the possibilities for adopting a collaborative, critical, and creative multilingual multiliteracies approach in TWI settings.